PERISTOMAL RECURRENCE OF LARYNGEAL CANCER (LITERATURE REVIEW) - A. O. Guz’; A. S. Zakharov; A. V. Garev (Опухоли головы и шеи)
Treatment of recurrent laryngeal cancer remains challenging for clinicians. Peristomal reccurence is one of the severest complications of laryngeal cancer that occurs in 2–15  % of patients after laryngectomy and has a poor prognosis: the two-year survival rate is 45 % in patients with stage I and stage II recurrence (according to G.A. Sisson) and 9 % among patients with stage III and stage IV recurrence. Stomal recurrence usually occurs within 2 years after surgery. The following factors can influence that: location of the tumor in the subglottic region of the larynx, size of the primary tumor, presence of regional metastases, placement of a tracheostoma before laryngectomy, and submucosal spread of the tumor to the trachea. All these factors should be taken into account in patients» management, including prescription of adjuvant therapy and choosing a treatment strategy in patients with primary disease.Since there are multiple factors that can influence peristomal reccurence development, the disease requires comprehensive evaluation in order to provide the most adequate treatment and to prevent stomal recurrence.